KAJIAN PENGGUNAANjALAT PENERANGANlJALAN TIPEILED DI JALAN BYfPASS MUNGGU TANAH LOT - Tri Juliarta, I Nyoman; Maharta Pemayun, A A Gd; Dyana Arjana, Gd (Jurnal SPEKTRUM, 2022)
The existence of public street lighting (APJ) as a means of supporting the road is very necessary to provide comfort, security, and safety for road users. Public street lighting that is not in accordance with the 2008 Indonesian National Standard (SNI) can cause road problems. SNI 2008 requires primary arterial roads to have an average illumination of 11-20 lux. The problem of lack of illumination occurs on the By Pass Munggu Tanah Lot road from the Seseh Beach traffic light intersection to the Singing beach road intersection, which has a length of 1.47 Km with a total of 21 street lighting points that produce an average illumination of 4,58 lux. The problem of harmonics in the electric power system is increasingly complex with the increasing use of non-linear equipment (eg LED lamps), where this equipment produces harmonics in voltage and current waves. In this study, harmonic calculations will be carried out on LED lamps and mercury lamps. The method used in the preparation of this research is a method of comparing the characteristics of mercury lamps and LED lamps, which is to compare from a technical and economic point of view. After that, match the provisions and conformity which in this case refers to SNI 2008.